"Meaning in the present": Understanding Sustainability for Digital Community Collections. Issue 1 (13th October 2021) - Fenlon, Katrina; Grimmer, Jessica; Reza, Alia; Thurston, Courtnie
Abstract: Living independently of mainstream institutions, digital community archives and digital humanities collections confront systemic barriers to medium‐ and long‐term viability. Their sustainability tends to be undermined by shifts in technologies, resources, and communities over time. Because these collections contain irreplaceable and invaluable evidence of communities and histories that are underrepresented in cultural institutions, their fragility compromises the completeness and equity of our collective digital heritage. Partnerships between institutions and community‐based collections often founder over a lack of shared understanding: of the expertise each partner brings to the table, of the scope and extent of mutual commitments, and of what sustainability even entails for a given project. This paper reports preliminary outcomes of a case study of the Lakeland Digital Archive, exploring how Lakeland's community understands sustainability in the context of their digital archive, as part of a broader study of community‐centered sustainability strategies for digital collections.